Accounting and accountability of waqf, zakat and Baitul Mal (WZB) in Malaysia: A review of literature - Sulaiman, Maliah; Mohamad, Muslim Har Sani; Abdul Rashid, Hafiz Majdi; Osman@Hussin, Ahmad Zamri; Siraj, Siti Alawiah; Nuhu, Ibrahim (Institut Perakaunan Negara, Jabatan Akauntan Negara Malaysia, 2016)
This article reviews literature on accounting and reporting for waqf, zakat and baitul mal (WZB). Given that WZB are under the purview of the State Islamic Religious Councils (SIRCs), the structure of the administrative machinery of Islamic affairs is discussed and how this gives rise to the unique demarcation in powers and authority on policies pertaining to Islam between the Federal and state governments is clarified. The notion of accountability as is generally understood in the West is elaborated and subsequently compared with the concept of accountability from Islam’s perspective. Prior studies on waqf and zakat examining the accounting and reporting aspects were reviewed. Issues such as poor documentation and record keeping, absence of sound accounting system, limited disclosure on the level and types of information, absence of separate financial statements are some of the pertinent findings of such studies. The paper also raises important questions about the validity of the current accounting practices of WZB and put forth various suggestions for future research. Finally, the initiative by the Accountant General's Department (AGD) to develop a financial accounting and reporting framework and standards for WZB is indeed laudable, timely and significant for the proper development of annual performance reporting of SIRCs. However, such an initiative should involve regulatory bodies such as the Jabatan Kemajuan Islam Malaysia (JAKIM), SIRCs as well as academics. Expertise from both accounting and Sharia should also be involved in this endeavour.